Means of automation of organizational and managerial process of extracurricular activities - A B Denisova (RUDN Journal of Informatization in Education, 2013)
Information and communication technologies improve the efficiency of management, so their introduction in the organizational and managerial processes of extracurricular activities is a necessity. A special place is occupied in the management of communication processes with the development of ICT have additional channels. Subject to the unification of requirements, resources, databases, programs used in the extracurricular field, can become part of an overall information system of the university.